Mandibular Distraction in Neonatal Pierre Robin Sequence: Is Immediate Extubation Both Feasible and Safe?. Issue 6 (12th April 2022) - Payne, Samuel H.; Brady, Colin M.; Mercury, Oblaise A.; Soldanska, Magdalena; Hush, Stefanie E.; Xiang, Yijin; Williams, Joseph K.
Abstract : Background: The timing of extubation following placement of mandibular distractors in the setting of Pierre Robin sequence is variable across institutional algorithms. Postoperative maintenance of intubation allows for an improvement in airway dimension and tongue positioning before extubation, theoretically decreasing the impact of postoperative airway edema. Maintenance of intubation, however, is not without risk. The authors analyze their institutional experience with neonatal mandibular distraction followed by immediate extubation to assess feasibility and safety profiles. Methods: A 4-year retrospective review of patients diagnosed with Pierre Robin sequence who underwent mandibular distraction within the first 3 months of life was performed. Patients intubated preoperatively were excluded. Results: Fifty-two patients met inclusion criteria. Thirty-eight patients (73 percent) were extubated immediately, whereas 14 patients (27 percent) remained intubated. No differences between these groups were found when comorbidities, cleft pathology, preoperative respiratory support, or grade of view on direct laryngoscopy were analyzed. Case duration greater than 120 minutes, operation start time after 3 pm, and the subjective designation of a difficult airway by the anesthesiologist were associated with maintaining intubation ( p < 0.05). Eight patients (21 percent) in the extubated group required an increase in respiratory support in the postoperative interval. Four of these patients (11 percent) required reintubation. Increased postoperative respiratory support was more likely in patients with certain comorbidities and higher preoperative respiratory support requirements ( p < 0.05). Conclusions: The authors' data suggest that immediate extubation following neonatal mandibular distraction is feasible in patients who are not intubated preoperatively. Careful consideration should be given to patients who require significant respiratory support preoperatively and in those with certain comorbidities. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.